INFECTION AND SYSTEMIC COMPLICATIONS BY PASTEURELLA SPP. IN A RABBIT: A CASE STUDY - Costa, Thayssa Duarte; Timoteo, Juliana Lyra; Magajevski, Fernanda Senter; Diniz, Jaqueline Assumpção (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
The coexistence of rabbits in parks and public recreation areas is a common scene; however, this interaction is not without risks as rabbits can be carriers of bacterial infectious diseases, posing a potential risk to public health. The Pasteurella genus, including Pasteurella multocida, plays a central role in developing bacterial infections that affect rabbits and other lagomorphs. Infection by this genus typically manifests with respiratory symptoms such as nasal discharge and sneezing, but the concern goes beyond that due to its zoonotic nature. These pathogens have the ability to be transmitted to humans, usually through bites, scratches, or direct contact, emphasizing the importance of careful management and preventive measures. Diagnosis in rabbits involves a comprehensive analysis, including clinical signs, medical history, laboratory tests, and specific tests. Symptoms such as nasal discharge, watery eyes, abscesses, and lethargy are common. Medical history and physical examination are crucial, along with the culture of samples and, when possible, serological tests. This case report describes the occurrence of pasteurellosis in a female rabbit treated at CRAS - Pró Arara "Raul de Barros Winter" in Araras, São Paulo, Brazil, highlighting the importance of surveillance, proper management, and awareness to mitigate public health risks associated with the coexistence of rabbits and humans in public recreation areas.